"CASE STUDY: THE MOST POPULAR METHOD FOR SOLVING SYSTEMS OF LINEAR EQUATIONS" - Kurniawan, Indra; Marfuah, Iim (Journal of Authentic Research on Mathematics Education (JARME), 2025)
The system of linear equations is a material that is studied from the junior high school level to the lecture level so that this material is very important material in learning mathematics. The purpose of this research is to find out what methods are easy and widely used by students in solving the system of linear equations. This research is a qualitative research with case study type. The participants of this study were 10 students of Indraprasta PGRI university. Data were collected by task-based interviews which aimed to dig deeper into the easiest and fastest method to solve the system of linear equations. The data analysis technique used in this study uses Bogdan Biklen technique with stages: data reduction, coding, determining themes, concluding. The results showed that there are 5 methods that can be used in solving the system of linear equations, namely: Cramer Method, Ajoin Matrix Method, Gaus Method, and Gaus Jordan Method. Of the four methods, according to the results of student tests, the best value is obtained with the Cramer Method, this is reinforced by the results of interviews conducted by students who said that the Cramer method is the easiest and fastest method to solve the system of linear equations. While the Gaus method is the most difficult method to solve the system of linear equations.Keywords: System of linear equations, Method, Case Study